EMPOWERMENT OF TOURISM BUSINESS IN MODOINDING- MINAHASA SELATAN - Evinita, Lenny Leorina; Philips Kambey, Joseph (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Tourism business actors have an important role to achieve the goals of the business being establish, without sufficient knowledge will reduce the desired achievement. The result of interviews conducted by the team on tourism businesses, they feel that they cannot continue their business because there is lack of awareness from tourism business actors to work together to promote their place of business. The problem found there were several problem which is lack of promotion, not work together and marketing system that effect the target. The target market has not been properly recorded , no attraction to bring guests to Modoinding, another problem is luck of funding support from banks and community business credit providers in Modoinding, The method used action research. The solution are the Modoinding Tourism community management has been formed , and worked to promoted and targeting visitors with integrated marketing system through regular events and promotion of Modoinding tourism one stop through a website, and other solution to support funds from BNI KUR system according to brochure. Conclusion: given education to tourism business actors, to have knowledge of promoting and managing finances for the businesses.